Design of Al-Mg-Si-Mn alloys with Zn, Cr and Sc additions with unique strengthening response - Trudonoshyn, Oleksandr (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2020)

Effect of Zr, Cr and Sc on the Al–Mg–Si–Mn high-pressure die casting alloys - Prach, Olena; Trudonoshyn, Oleksandr; Randelzhofer, Peter; Körner, Carolin; Durst, Karsten (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2019)
New aluminium Al5Mg2SiMn casting alloys with Sc, Cr, Zr addition have been developed. The effect of the alloying elements in amount of 0.1 and 0.2 wt.% on the microstructure and mechanical properties of the Al5Mg2SiMn casting alloy produced by the HPDC was investigated. The microstructure was observed by means of the scanning electron microscopy and electron probe microanalysis. The hardness of the aforementioned alloys was determined by Brinell and nanoindentation testing. The microstructure of the HPDC aluminium alloys consists of primarily α-Al phase, the α-Al15(Mn,Fe)3Si2 intermetallics and Al-Mg2Si eutectic cells. Coarse Al7Cr as well as Al3Zr intermetallic phases in the alloys with Cr and Zr addition were observed. The most significant improvement in the mechanical properties was achieved in the alloys with Sc addition. Alloying with 0.2 wt.% of Sc exhibits the best combination of strength and ductility with a yield strength of 196 MPa, an ultimate tensile strength of 341 MPa and 10 % of elongation in the as-cast condition. Alloys with Cr and Zr additions present the similar properties in terms of hardness compared to the alloys with Sc addition and the similar tensile properties comparable to the AlMg5Si2Mn (commercially known as “Magsimal-59”) base alloy.
Keywords: Al-alloys; Chromium; Zirconium; Scandium; Microstructure; Mechanical properties

Heat treatment of high-pressure die casting Al-Mg-Si-Mn-Zn alloys - Trudonoshyn, Oleksandr; Randelzhofer, Peter; Körner, Carolin (Journal of Alloys and Compounds, 2021)
The microstructure and mechanical properties of Al-5.7Mg-2.6Si-0.7Mn-xZn high-pressure die casting alloys after heat treatment have been investigated. The microstructure was studied by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The hardness was determined by Brinell and Vickers testing. The effects of T5 (artificial ageing from the as-cast state) and full T6 heat treatment modes on the alloys with different Zn content (0.6…5 wt.%) on the microstructure and mechanical properties were investigated. The solution treatment changes the microstructure of the studied alloys. The T-AlMgZn phase dissolves into the α-Al phase during solution treatment at temperatures higher than 375ºC. Artificial ageing at 125-225ºC doesn’t lead to any changes in the microstructure of alloys, however, leads to the formation of several types of Zn-containing precipitates in the α-Al. The optimal temperature for artificial ageing from the as-cast state as well as after solution treatment is in the range 125-175ºC for 2-5 h. It was found that the most noticeable changes in the mechanical properties were achieved in the alloys with 1.2-1.8 wt.% Zn. It was found that these changes are associated with Zn distribution, the morphology of the phases and the formation of nano-sized precipitates in α-Al solid solutio
Keywords: Al-Mg-Si-Mn-Zn alloys; heat treatment; precipitation strengthening; mechanical properties

Heat treatment of the new high-strength high-ductility Al–Mg–Si–Mn alloys with Sc, Zr and Cr additions - Trudonoshyn, Oleksandr; Prach, Olena; Randelzhofer, Peter; Durst, Karsten; Körner, Carolin (Materialia, 2020)
Heat treatment of alloys of the Al–Mg–Si system essentially affects the age-hardening response and, accordingly, their final mechanical properties. However, the specific Mg/Si ratio in casting alloys makes age-hardening by heat treatment negligible. To improve the age-hardening response, the alloys were alloyed with Sc, Cr, Zr, and two types of heat treatment were applied: full T6 (solution treatment (ST), quenching, and artificial aging (AA)); and T5 with AA from the as-cast state. The microstructure after different heat treatment modes was observed by means of SEM and TEM. It was established that the main structural components that affect the mechanical properties of alloys after heat treatment are nanoscale precipitates and a coarse Al 7 Cr and Al 3 Zr intermetallic phases in the Cr- and Zr-containing alloys. The highest impact in terms of tensile properties was achieved in the Sc-containing alloys after T5 at 325 °C. Alloys with 0.2 wt% Sc exhibit the highest strength after T5 from as-cast state at 325 °C (up to 380 MPa) and highest elongation (up to 20%) after full T6 (ST 520 °C and AA 325 °C). <br
Keywords: Al–Mg–Si alloys; Heat treatment; Mechanical properties; Scandium addition

Improvement of the high-pressure die casting alloy Al-5.7Mg-2.6Si-0.7Mn with Zn addition - Trudonoshyn, Oleksandr; Rehm, Sebastian; Randelzhofer, Peter; Körner, Carolin (Materials Characterization, 2019)
The microstructure and mechanical properties of the high-pressure die casting alloys Al-5.7Mg-2.6Si-0.7Mn-xZn in as-cast condition have been investigated. The microstructure was studied by scanning electron microscopy (SEM), electron probe microanalysis (EPMA) and transmission electron microscopy (TEM). Intermetallic particles and volume fractions were measured using partly automated image analysis in the software Fiji/Imagej. Results of the microstructure analysis were compared with Thermo-Calc calculations. The hardness was determined by Brinell (HB) and local properties were determined by Vickers (HV0.01) testing. The ultimate tensile strength (UTS), yield strength (YS) and elongation were performed by conventional tensile tests at room temperature. The microstructure of the studied alloys consists primarily of α-Al phase, the α-AlFeMnSi intermetallics, Al–Mg2Si eutectic cells. Addition of Zn leads to the formation in the structure T-AlMgZn phase. The higher Zn content in the alloy the higher volume fraction of T-AlMgZn phase. The increasing of Zn content in the alloy leads to its increasing in α-Al accordingly. The addition of 1.2–1.8 wt% Zn to the base alloy caused the most significant changes in mechanical properties. Alloying up to 1.2 wt% Zn shows the improvement of strength and hardness while the elongation value remains at the same level as in the base alloy. Alloying with 1.8 wt% Zn shows the highest level of strength (380 MPa of UTS) but the level of elongation decreased. With further increase of Zn concentration the YS and HB continued their growth (up to 270 MPa of YS and 120 HB) whilst elongation and UTS decreased.
Keywords: Al-Mg-Si alloys; Age hardening; Precipitates; Microstructure; Mechanical properties

Morphology and Nucleation of Intermetallic Phases in Casting Al–Mg–Si Alloys - Slyudova, Anna; Trudonoshyn, Oleksandr; Prach, Olena; Lisovskii, Vitaliy (Metallography, Microstructure, and Analysis, 2020)
The changes in the structure of Al–Mg–Si casting alloys after additional alloying are observed. In order to predict and to explain with greater confidence, the phase transformations in the studied alloys equilibrium phase diagrams were calculated using Thermo-Calc software. The results of the Thermo-Calc are in good agreement with the microstructure analysis. Morphology and chemical composition of intermetallic phases were investigated by scanning electron microscopy, energy-dispersive x-ray analysis, and electron probe microanalysis on polished and deep etched microsections. Several intermetallic phases with Fe and Mn, phases that contain Zn and Cu, and Al3Ti crystals were described. It was found that the addition of Mn changes the morphology of Fe-containing intermetallics that improve strength and ductility of the alloys; crystals Al3Ti can act as nucleating particles of α-Al dendrites; Cu and Zn lead to the formation of several fusible eutectic phases. To better understand the influence of the different intermetallics, the mechanical properties (Brinell hardness, ultimate tensile strength, yield strength, elongation) were measured. Alloying with Cu and Zn exhibits the best values of hardness and strength (up to 85 HB and UTC = 251 MPa), while the highest ductility was achieved in the alloy with composition Al–5.5Mg–2.5Si–0.6Mn (6.7%). Alloys possess the lowest properties (both strength and ductility) with the highest concentrations of Fe and Si (UTS up to 173 MPa with elongation 3.4%).
CRIS-Team Scopus Importer:2020-12-11
Keywords: Aluminum alloys; Intermetallics; Microstructure; Multistep nucleation; Phase diagrams

Multi-alloying effect of Sc, Zr, Cr on the Al-Mg-Si-Mn high-pressure die casting alloys - Prach, Olena; Trudonoshyn, Oleksandr; Randelzhofer, Peter; Körner, Carolin; Durst, Karsten (Materials Characterization, 2020)
The alloying effects of small additions of Sc, Zr, Cr on the microstructure and mechanical properties of Al-5Mg-2Si casting alloys produced by High Pressure Die Casting (HPDC) were investigated. The microstructure of the Al-alloys consists primarily of the α-Al and Al-Mg2Si eutectic cells and the α-Al15(Mn,Fe)3Si2 intermetallic phase as well as coarse Al7Cr and Al3Zr intermetallic phases. The most significant improvement in the mechanical properties was achieved in the alloys with Sc + Cr and Sc + Zr additions. Alloying with 0.2 wt% of Sc in combination with Zr and Cr additions exhibits the best combination of strength and ductility with a yield strength of 206 MPa, an ultimate tensile strength of 353 MPa and an elongation of 10% in the as-cast condition. Alloys with Cr + Zr addition have a higher hardness and tensile strength compared to the AlMg5Si2Mn base alloy (commercially known as “Magsimal-59”) and the similar levels of yield strength and elongation. However, they have lower levels of all set of properties compared to the alloys with Sc + Cr and Sc + Zr additions, due to the presence of coarse Al7Cr sludge and Al3Zr intermetallic phase
Keywords: Al-alloys; HPDC; Chromium; Zirconium; Scandium; Mechanical properties

Multistep nucleation and multi-modification effect of Sc in hypoeutectic Al-Mg-Si alloys - Trudonoshyn, Oleksandr; Prach, Olena (Heliyon, 2019)
Structure of Al5Mg2SiMn casting alloy with and without of Sc addition, morphology of primary phases and specifically morphology of the Sc-containing intermetallic compounds and nanoscale properties of the alpha-Al matrix of Al-Mg-Si-Mn alloys were observed. Morphology and chemical composition were investigated by scanning electron microscopy on polished and deep etched microsections.
CRIS-Team WoS Importer:2019-03-20

Structure formation and multistep nucleation in Casting Al-Mg-Si alloys - Trudonoshyn, Oleksandr; Prach, Olena; Slyudova, Anna; Lisovskii, Vitaliy (International Journal of Cast Metals Research, 2020)
The process of multistep nucleation during solidification in hypoeutectic Al-Mg-Si casting alloys was investigated. The morphology of the nucleating particles, Mg2Si primary crystals and Al-Mg2Si eutectic, was investigated with scanning electron microscopy (SEM) on polished and deep etched microsections. The mechanism of formation of the Mg2Si crystal was attributed to heterogeneous nucleation on the nucleating particles. It was observed that the majority of the alloys particles found in the studied are oxides. It was established that eutectic Al–Mg2Si in hypoeutectic alloys has the morphology of ‘eutectic crystal’, where one face of the crystal has triangular-spiral morphology. The mechanism of formation of Al-Mg2Si eutectic cells is attributed to epitaxial growth on Mg2Si crystals. The microhardness of the structural components (Mg2Si crystals, α-Al dendrites, Al-Mg2Si eutectic, and Al3Ti crystals) was measured using Vickers hardness tester.
CRIS-Team Scopus Importer:2020-09-25
Keywords: Al-alloys; heterogeneous nucleation; multistep nucleation; nucleating particles; primary crystals; spiral eutectic

Studying the Structure of Al–Mg–Si Casting Alloys Doped by Lithium - Trudonoshyn, Oleksandr (Physics of Metals and Metallography, 2020)
Abstract: The article discusses changes in the structure of Al–Mg–Si cast alloys after their additional alloying with lithium. To predict and explain the phase transformations in the studied alloys, phase diagrams were calculated using Thermo-Calc software. Thermo-Calc results are in good agreement with microstructure analysis. The morphology and chemical composition of the intermetallic phases were studied using a scanning electron microscope and EDX analysis on polished and deeply etched microsections. There were revealed several intermetallic phases in the studied alloys. It was found that the addition of lithium has a modifying effect on the structure of the studied alloys, which also leads to the formation of a new AlLiSi phase. To analyze the effect of lithium on the mechanical properties, the Brinell hardness, tensile strength, yield strength, and elongation were measured. Additional alloying with lithium leads to an increase in the strength properties of the studied alloys compared to the base alloy.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Al–Mg–Si alloys; lithium; microstructure; phase diagrams